AN ANALYSIS OF STUDENTSâ SKILL IN USING CONJUNCTION IN RECOUNT TEXT AT TENTH GRADE STUDENTS OF SMAN 3 RAMBAH HILIR - -, HELMI; Donal, Andri; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
The purpose of this research is to analyze the studentsâ skill in using conjunction in recount text. Thisresearch was descriptive qualitative research and used test as instrument in collect the data. The result of thisresearch showed that the studentâ skill in using coordinating conjunction was 60,6% or in fair category and studentsskill in using subordinating conjunction was 65,6 or in fair category. The result of this research was 60,4 it can beconclude that the studentsâ skill was in fair category